Rumor, sarcasmo y burla en el desastre lento: Lectura de la narrativa argentina reciente sobre y desde la diversidad funcional - Gasel, Alejandro Fabian (2024)
This chapter explores the textualities that thematize disability in their uses of language linked to humor through rumors, mockery, and sarcasm used in different enunciative policies within travel or biographical narratives such as María Moreno’s: Banco a la sombra (2019) or Aurora Venturini’s: Las amigas (2020) or Verónica Suckazer’s: Entre dos mundos, mi vida como hipoacúsica (2018). In this framework, different interventions by authors who write from disability and enunciate from that agency (Suckaczer or Silvestri) bring about a type of discursivity marking the obstructive and moralizing conditions that both State and Parastate enabling devices place on bodies outside the norm. Added to this is the study of humor as a strategy where subalternity can sneak in and alter the strategies and tricks to turn around the moralizing discourses that pigeonhole bodies. In this chapter, humor, subalternity, and disability form an alliance that is placed on the stage where agents and their statements show that laughter goes hand in hand with resistance and joyful passions.